The Metaphysics of Touch: Remarks on the Margins of Richard Kearney’s Touch - Sieczkowski, Tomasz (Hybris, 2025)
This paper examines Richard Kearney’s book Touch: Recovering our most vital sense, analysing how Kearney positions touch as our most fundamental sense in an increasingly digital and disembodied world. The author first contextualizes Kearney’s work within recent empirical and philosophical research on touch, comparing it with approaches by Fulkerson, Linden, Banissy, and Classen. The paper then explores Kearney’s central concept of tact, which represents a special bodily intelligence that precedes abstract knowledge and serves as the foundation for all sensory experience. Through philosophical analysis drawing on Aristotle and phenomenological traditions, Kearney challenges the dominant Western opto-centric tradition that privileges sight over touch. The author highlights Kearney’s argument that touch has healing potential through the archetype of the “wounded healer” and discusses how Kearney proposes a balanced integration of physical and virtual experiences to counter the modern process of excarnation (i.e. disembodiment). The paper concludes that Kearney’s rehabilitation of touch represents not just a philosophical project but an urgent cultural imperative for reintegrating our individualized selves and communities through embodied contact.